Hattie Ellis: Eating England - Davidson, Alan (Petits Propos Culinaires, 2024)
Hattie Ellis: Eating England: Mitchell Beazley, London, 2001: ISBN 1-84000-351-0: 304 pp., many b&w photos by Jill Mead, h/b, £14.99.